Human Factor as Cause of Aviation Accidents - Hrdinová, Lenka; Němec, Vladimír (My University, 2018)
Aviation safety should be a highest priority for all subjects involved in civil aviation. As in any other transport system, however, it can not be ensured that no extraordinary events such as incidents and accidents will occur. Aviation incidents and accidents arise for a variety of reasons, and the human factor plays a key role in its occurrence. The issue of human factor and its relationship to the aviation safety is the subject of this paper which describes safety development and other important aspects of safety in relation to the human factor and then analyzes the number of aviation accidents and their causes.
Lidský činitel jako příčina leteckých nehod
Keywords: human factor in aviation; safety; accident; lidský činitel v letectví; bezpečnost; nehody